Low Power Tree Network Implementation Using Bluetooth Low Energy Multirole - Díaz, Leandro; Steinfeld, Leonardo; Seré, Andrés; Oliver, Juan Pablo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2024: Anais do XIV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2024)
This paper presents an implementation of a low power tree network solution based on Bluetooth Low Energy (BLE) device that form a tree-link topology using multirole. BLE is typically employed in star topologies, which limits its range to the maximum distance of the radio link. To overcome this limitation and extend the range while maintaining low power consumption, this work utilizes a tree topology with BLE connections. By employing a connection-oriented approach, nodes are synchronized to exchange data, minimizing their radio activity and significantly improving energy efficiency and battery life. The implementation details, including node roles and the tree formation process, are discussed. The experimental results show that the BLE tree network achieves low power consumption across all nodes, making it suitable for various IoT applications requiring extensive coverage and long battery life. We include a comparative analysis with other BLE protocols, to demonstrate the superior energy efficiency of the proposed system.